Studi Komparatif Tingkat Perkembangan Wilayah Perdesaan di Kabupaten Bengkalis - Harimurti, Kingkin Aji; Mutha’ali, Lutfhi; Kurniawan, Andri (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2024)
Decentralization has reinforced the development paradigm based on the geographical characteristics of the region (endegenous development). Bengkalis Regency is one of the regencies with varied regional shapes, so it is necessary to study the disparity in development levels based on their geographical characteristics. Composite index and discriminant analysis were used to examine the disparity and factors that determine the level of regional development. The results showed that the level of development of rural areas in Bengkalis Regency was predominantly low 62.58%, medium 23.23% and high 14.19%. The level of development of the plain area is higher than that of the coastal area, Bengkalis Island and Rupat Island. Population growth, population density and the number of cellular operator services that can reach are the variables that determine disparity in regional development in Bengkalis Regency.